Glycosylated platycosides: Identification by enzymatic hydrolysis and structural determination by LC–MS/MS. Issue 1 (11th December 2013) - Jeong, Eun‐Kyung; Ha, In Jin; Kim, Yeong Shik; Na, Yun‐Cheol
<x xml:space="preserve">Abstract</x> In this study, enzymatic hydrolysis and chemometric methods were utilized to discriminate glycosylated platycosides in the extract of Platycodi Radix by LC–MS. Laminarinase, whose enzymatic activity was evaluated using gentiobiose and laminaritriose, was a suitable enzyme to identify the glycosylated platycosides. The laminarinase produced deapi‐platycodin D and platycodin D from the isolated deapi‐platycoside E and platycoside E through the loss of two glucose units by enzymatic reaction, respectively. After hydrolyzing a crude extract by laminarinase, the reconstructed total ion chromatogram generated by a chemometric technique sorted peaks of deglycosylated platycosides easily. Structural information of the glycosylated isomers was revealed through fragment ions generated by the sodiated C0β ion corresponding to reduced disaccharides in the positive MS4 spectra. Characteristic fragment ions of Glc‐(1→6)‐Glc moieties were observed through ring cleavages of 0, 2A0β, 0, 3A0β, and 0, 4A0β, whereas Glc‐(1→3)‐Glc moieties produced only 0, 3A0β ions. Lithium‐adducted platycosides allowed more detailed structural analysis of glycosidic bond cleavage corresponding to Y1β and B1β in addition to ring cleavage.